Analysis of Microbiota Structure and Potential Functions Influencing Spoilage of Fresh Beef Meat - Hwang, Bo Kyoung; Choi, HyeLim; Choi, Sang Ho; Kim, Bong-Soo (Frontiers in Microbiology, 2020)
Beef is one of the most consumed food worldwide, and it is prone to spoilage by bacetria . This risk could be caused by resident microbiota and their alterations in fresh beef meat during processing. However, scarce information is available regarding the potential spoilage factors due to resident microbiota in fresh beef meat. In this study, we analyzed the microbiota composition and their predicted functions on fresh beef meat. A total of 120 beef meat samples (60 fresh ground and 60 non-ground beef samples) were collected from three different sites in South Korea and different months, and the microbiota was analyzed by the MiSeq system. Our results showed that although the microbiota in beef meat were varied among sampling site and months, the dominant phyla were the same with shared core bacteria. Notably, psychrotrophic genera, related to spoilage, were detected in all samples, and their prevalence increased significantly in July. These genera could inhibit the growth of other microbes with using glucose by fermentation. Results of this study extend our understanding of initial microbiota in fresh beef meat and potential functions influencing spoilage, and can be useful to develop the preventive measures to reduce the spoilage of beef meat products.